TEKNIK BUDIDAYA IKAN BANDENG DI KABUPATEN DEMAK - Ahmad Romadon; Endah Subekti (MEDIAGRO, 2011)
Milkfish (Chanos Chanos Forsskal) is a popular food fish in Southeast Asia, milkfish has a long body, slender, solid, flat, and oval, like a torpedo. Fish, including fish species eurihalin, so the fish can be found in freshwater, brackish water and seawater. During the period of its development, like the fish live in brackish water or river estuaries, as an adult fish return to sea to breed. This study aims to determine the fish farming techniques  in  Demak  Regency, know the techniques of treatment ponds are often exposed to rob or sinking tide, knowing the post-harvest fish handling and marketing. This research was conducted by following the direct method of milkfish aquaculture activities in Demak Regency, also conducted interviews with the farmers to dig deeper. For purposes of comparison and complementary in solving the problem, obtained from literature searches. Fish cultivation in Demak Regency generally still done traditionally by simply relying on the natural course of feeding so that optimal results are not yet able to make ends meet, so that fish farming is just as a sideline only. To cope with the condition of ponds are often exposed to rob the farmers put up during a waring to rob the fish do not escape into the sea. Need for intensive counseling to farmers to enable them to manage better the fish ponds that provide a more optimal for dijadika source of livelihood for them. Key words: fish, aquaculture, fish farmers, Demak Regency